IMPLEMENTASI KEBIJAKAN RETRIBUSI PELAYANAN PERSAMPAHAN/KEBERSIHAN DI KOTA PASANGKAYU KABUPATENMAMUJU UTARA - Norhana, Norhana (Katalogis, 2016)
This study aims to identify and describe the policy implementation levy Pasangkayu waste services in the city of North Mamuju regency. This type of research is qualitative. The informants are officers of Housing and Spatial Planning and the community in the City Pasangkayu. Collecting data using observations, interviews, and documentation, while data analysis using data reduction, data presentation, drawing conclusions/verifikasi.Hasil research shows the retribution policy implementation Pasangkayu waste services in the city has not shown that the maximum performance, because the aspects studied such as the size and purpose , resources, and the economic environment, social, political and not running optimally. The size and purpose of the policy is not maximized due to budget constraints resulted in a lot of programs that have not been accommodated in the work plan the budget so that policy implementation is not maximized as the size and purpose. Resources are limited, be it human resources, facilities and infrastructure and the budget provided, sertalingkungan economic, social and politikbelum fully support, because of the attitude of the public is less aware of the implementation of the policy, even related parties such as the government is still less strict in following up civil disobedience the implementation of policies.